Peran Sekolah Dalam Upaya Pencegahan, Pemberantasan Penyalahgunaan,dan Peredaran Gelap Narkoba - Marhaeni Fajar Kurniati; Rakhmadiansyah Rakhmadiansyah; Erdyan Jaya Maulana; Takdir Ali Syahbana; Farihin Farihin; Alfi Syahrin (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
The community service activity "The Role of Schools in Preventing, Eradicating Abuse and Illicit Drug Trafficking" was carried out on Thursday 16 November 2023, which was attended by 35 students representing class 10 and class 12 of the Vocational High School (SMK) Technology Education Foundation (YPT) Banjarmasin. The activity was carried out in several stages, namely: an opening led by an emcee from the school, remarks from the Deputy Head of SMK YPT Banjarmasin for Student Affairs, Sahri, as well as remarks from the Lecturer in Communication Perspectives and Theory at the Uniska Banjarmasin Communication Science Masters Study Program, Dr. Marhaeni Fajar Kurniawati, M.Si. Then the peak event was the socialization of the delivery of material entitled The Role of Schools in Preventing, Eradicating Abuse and Illicit Drug Trafficking which was delivered by the Chief Executive of Community Service, Rakhmadiansyah, then a question and answer or quiz, and the distribution of prizes for students who actively asked questions. This service activity is a form of concern for the Uniska Banjarmasin Communication Science Masters Study Program to provide understanding and education to YPT Banjarmasin Vocational School students about the dangers and impacts of drug abuse as well as the role that the school must take in creating a school free from drug abuse (Shining School).